ANALYSIS OF CLASSROOM INTERACTION IN EFL CLASS - Asbah Asbah (Muhammadiyah University of Mataram, 2015)
This study was to find out classroom interaction types and how those types emerge in the language teaching process. The research design was a qualitative descriptive. Participants of the research were an English teacher and 25 eight grade students of MTs-Al Raisiyah Sekarbela. The results of the study showed that there were seven types of classroom interactions which were teacher-whole class, teacher- an individual student, teacher-groups of students, student- teacher, student-student, student-whole class, and student-groups of students. The interaction occurred through teacher talk, questioning, giving feedback and discussion.